Barriers of occupational safety implementation in infrastructure projects: Gaza strip case - Abu Aisheh, Y.I. (MDPI AG, 2021)
Infrastructure projects are the foundation for essential public services and have an influential position in societal development. Although the role of infrastructure projects is substantial, they can involve complexities and safety issues that lead to an unsafe environment, and which impacts the project key stakeholders. Therefore, this study aimed to evaluate the barriers to implementing occupational safety in infrastructure projects in the Gaza Strip, which cause serious threats and reduce project performance. To evaluate the barriers, 39 items were highlighted and modified as per the construction context and environment, and which later were distributed in the form of a questionnaire, to get feedback from consultants and contractors. The analysis shows that in the safety policy barriers group, consultants and contractors both ranked the item âa contractor committed to an occupational safety program is not rewardedâ first. In the management barriers group, consultants and contractors both ranked the item âsafety engineer does not have significant powers, such as stopping work when neededâ in the first place. In the behavior and culture barriers group, consultants and contractors both ranked the item âworkers who are not committed to occupational safety are not excludedâ in the first place. Overall, both consultants and contractors shared the same viewpoint in classifying the barriers in the working environment. The outcome of this study is beneficial for Palestinian construction industry policymakers, so they can monitor the highlighted barriers in on-going infrastructure projects and can modify the safety guidelines accordingly. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.